Examining Commitment to Prevention, Equity, and Meaningful Engagement: A Review of School District Discipline Policies. (July 2021) - Green, Ambra L.; Hatton, Heather; Stegenga, Sondra M.; Eliason, Bert; Nese, Rhonda N. T.
Although there is increasing awareness of policy decisions contributing to disproportionality in exclusionary practices, few studies have empirically examined common elements of discipline policies across the nation. We utilized a methodological review and the Checklist for Analyzing Discipline Policies and Procedures for Equity (CADPPE) to examine the extent to which current policies reflect recommendations from research regarding best practices for encouraging appropriate behaviors and preventing undesired behaviors, as well as correlations between those policies and exclusionary disciplinary outcomes for all students of color and students of color with disabilities. Data came from 147 district discipline policies and disciplinary outcomes (i.e., suspension and expulsion) from all 50 U.S. states and the District of Columbia. The analyses indicated the majority of policies do not include most of the research-based recommendations for preventing the overuse of exclusionary practices. Furthermore, there was no correlation found between CADPPE ratings and the risk ratios for exclusionary discipline for students of color and students of color with disabilities. Implications for policy development and implementation and limitations are provided.